Mutation in ADAT3, encoding adenosine deaminase acting on transfer RNA, causes intellectual disability and strabismus. Issue 7 (25th April 2013) - Alazami, Anas M; Hijazi, Hadia; Al-Dosari, Mohammed S; Shaheen, Ranad; Hashem, Amal; Aldahmesh, Mohammed A; Mohamed, Jawahir Y; Kentab, Amal; Salih, Mustafa A; Awaji, Ali; Masoodi, Tariq A; Alkuraya, Fowzan S
Abstract : Background: Intellectual disability (ID) is one of the most common forms of disability worldwide, displaying a wide range of aetiologies and affecting nearly 2% of the global population. Objective: To describe a novel autosomal recessive form of ID with strabismus and its underlying aetiology. Materials and methods: Autozygosity mapping, linkage analysis and exome sequencing were performed in a large multiplex consanguineous family that segregates ID and strabismus. Exome sequencing was independently performed in three other consanguineous families segregating the same disease. Direct sequencing of the resulting candidate gene was performed in four additional families with the same phenotype. Results: A single missense mutation was identified in ADAT3 in all studied families on an ancient ancestral haplotype. This gene encodes one of two eukaryotic proteins that are necessary for the deamination of adenosine at position 34 to inosine in t-RNA. Our results show the first human mutation in the t-RNA editing machinery and expand the landscape of pathways involved in the pathogenesis of ID.